LATAR BELAKANG DAN KEPENTINGAN NASIONAL KOREA SELATAN DALAM KEBIJAKAN CROSS CERTIFICATION MAKANAN HALAL DENGAN UNI EMIRAT ARAB (2015-2017) - Wibisono, Juwita Dewi Arimbi (Global and Policy Journal of International Relations, 2018)
This study explores South Korea‟s “cross certification” foreign policy, explaining the development of halal food industry in the country. Recently, the Halal food industry has become a huge market, attracting attentions in the global market. In this case, South Korea has been chosen as an interesting example because its‟ very minor Muslim population. From the total 51 million of its population, Muslim only counted as 250.000, representing less than 1% of them. Despite the very small number of Muslim, South Korea had made a serious efforts through certification cooperation with United Arab Emirates (UAE) in 2015. Therefore, this paper examines the interests of South Korea through cross certification with UAE. Findings are followed through an analysis by the lenses of national interest concept and rational choice theory. This research explores three findings of the background and interest in the cooperation that could be explained. First, a very high import demand in the Emirates. Secondly, interest in ESMA (Emirates Authority of Standardization and Metrology) certification, the best quality standardization acknowledged in the Middle East and North Africa (MENA) region. Lastly, this study provides that the case was driven by economic interest and export activities which are mutually intertwined.DOI: https://doi.org/10.33005/jgp.v6i02.1825 Keywords: Export, Cross Certification, Halal Food, South Korea, United Arab Emirates